2013
DOI: 10.1523/jneurosci.3219-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Distal Dendritic Inputs Control Neuronal Activity by Heterosynaptic Potentiation of Proximal Inputs

Abstract: Synaptic inputs onto distal dendritic tufts are believed to function by modulating time-locked proximal inputs. However, little is known about the function of these inputs when proximal synapses are not coincident or silent. Surprisingly we found that activation of apical tuft synapses alone resulted in heterosynaptic potentiation of proximal synapses. In mouse adult hippocampal CA1 pyramidal neurons, we show that activation of distal inputs from the entorhinal cortex specifically strengthens proximal synapses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…Previous data suggest that, in contrast to synapses in the MOB, a large number of AOB synapses are rich in the GluN2B subunit of NMDARs (Dani et al, 2010). Whether similar rules apply to AOB and CoA synapses on MeA neurons awaits future studies using dendritic recording (Andrasfalvy and Magee, 2001) or nanoscale imaging of labeled glutamate receptors at these synapses (Nicholson et al, 2006;Dani et al, 2010). Moreover, potential spillover of glutamate to neighboring extrasynaptic NMDARs, which is thought to promote the generation of dendritic NMDA spikes (Chalifoux and Carter, 2011), may also play a part.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous data suggest that, in contrast to synapses in the MOB, a large number of AOB synapses are rich in the GluN2B subunit of NMDARs (Dani et al, 2010). Whether similar rules apply to AOB and CoA synapses on MeA neurons awaits future studies using dendritic recording (Andrasfalvy and Magee, 2001) or nanoscale imaging of labeled glutamate receptors at these synapses (Nicholson et al, 2006;Dani et al, 2010). Moreover, potential spillover of glutamate to neighboring extrasynaptic NMDARs, which is thought to promote the generation of dendritic NMDA spikes (Chalifoux and Carter, 2011), may also play a part.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies in pyramidal neurons have shown that distal synapses can impact the gain and plasticity of proximal inputs (Remondes and Schuman, 2002;Dudman et al, 2007;Han and Heinemann, 2013). In CA1 pyramidal neurons, for instance, closely timed activation of the distal perforant path and the proximal Schaffer-collateral synapses induces potentiation of the latter (Dudman et al, 2007). Thus, it is likely that, through a similar mechanism, an association between main and accessory olfactory inputs will be formed in MeA principal neurons, leading to odor-evoked responses driven by pheromonal cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two major inputs can either cooperate or compete, depending on the nature of the task (Dvorak-Carbone and Schuman, 1999a, 1999b; Remondes and Schuman, 2002; Golding et al, 2002; Dudman et al, 2007; Han and Heineman, 2013). During the recall phase (center arm) of the T maze task, the CA3 and EC3 inputs may cooperatively increase their influence on CA1 (Montgomery and Buzsáki, 2007; Yamamoto et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Theta-burst stimulation of distal CA1 input induces a LTP of proximal input without affecting distal inputs, while low frequency stimulation of distal inputs induces LTD at distal inputs and LTP at proximal inputs (Han & Heinemann, 2013;Wöhrl, Haebler, & Heinemann, 2007). Furthermore, in area CA2 we have shown that HFS of proximal input induces iLTD allowing a lasting increase in both the E/I ratio and the firing of CA2 neurons in response to both proximal and distal excitatory input stimulation (Nasrallah et al, 2015;Piskorowski & Chevaleyre, 2013).…”
Section: Activity Of Distal Input To Ca2 Opens the Gate Between Ca3 Amentioning
confidence: 67%